2004
DOI: 10.2214/ajr.182.4.1821059
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Bilateral Breast and High-Resolution Axillary MRI of Patients with Breast Cancer: Preliminary Results

Abstract: Breast tissue and axillary lymph nodes both can be analyzed on MRI in a one-step process using a bilateral breast coil combined with a surface coil. Morphologic features observed on high-resolution MRI of the axilla can improve the identification of metastatic nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 29 publications
2
37
0
1
Order By: Relevance
“…Moreover, Luciani et al [5] reported significantly higher enhancement in the invaded lymph nodes than in those with negative pathologic findings.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, Luciani et al [5] reported significantly higher enhancement in the invaded lymph nodes than in those with negative pathologic findings.…”
Section: Discussionmentioning
confidence: 97%
“…Luciani et al [5] found that the best discrimination between pathologic and negative findings were the presence of irregular contours, high signal intensity on T2 and marked gadolinium enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…The studies are mostly about enhancement and MRI characteristics of the lymph nodes (11-15). In a study by Luciani et al, (11) high-resolution MRI of the axilla and bilateral breast MRI was evaluated in order to identify nodal lymph node features and metastatic involvement.…”
Section: Discussionmentioning
confidence: 99%
“…This is also well in correlation with our study. In study by Luciani et al [35] also eccentric or irregular cortical thickening and non visualization of hilum was seen as having a high positive predictive value for nodal metastasis. They also showed that irregular nodal margin was correlating well with extracapsular extension.…”
Section: Axillary Lymphadenopathymentioning
confidence: 83%